My life for the poor - Teresa, Mother; Gonzalez-Balado, Jose Luis. (New York : Ballantine, 1989)
Gathers into one volume what she has said and written about her life, her work, her faith, and the spiritual joy she has found.
Young Adult
Keywords: Teresa, Mother, -- 1910-; Teresa, Mother, -- 1910; Church work with the poor; Missionaries of Charity -- Biography; Church work with the poor; Missionaries of Charity -- Biography